Determining the perceived acceptability of an intervention designed to improve health literacy around developmentally appropriate play during infancy, with a community advisory group of mothers, in Soweto, South Africa. - Fiona Bennin; Helene Theunissen; Shane A Norris; Alessandra Prioreschi (PLOS Global Public Health)
Children require opportunities to participate in unstructured, unrestricted active play as infants, to encourage positive health, socioemotional and developmental outcomes in life. Certain social and environmental factors in the home setting can limit participation in play, particularly in low resource settings. As caregivers are their infants' first teachers, they have the important role of providing opportunities and space for children to learn through play. This mixed methods, cross-sectional study aimed to test the acceptability of an intervention developed to improve health literacy around play and development with mothers from Soweto, South Africa. Fifteen mothers with infants aged 0-3 months were included to form a Community Advisory Group (CAG). Two rounds of focus group discussions (FGDs) were conducted to explore the understanding of, and barriers to play and development, and to determine the acceptability of an intervention prototype. The prototype included developmentally appropriate activities presented in video format, demonstrations of how to make toys, infographics and other educational material which would be delivered to participants as part of the intervention. A further questionnaire was administered to participants one week after the FGD to determine the acceptability of intervention activities which the participants completed at home, with their infants. Participants reported several barriers to play, including limited options for safe outdoor play, overcrowding, insufficient time, limited resources, and conflicting information. Participants suggested that the intervention content be delivered every 1-2 weeks, through a data-free app. Overall, the prototype activities tested at home were deemed acceptable. The reported barriers, together with reduced motivation and self-efficacy observed in the participants, guided the researchers to develop intervention content focused on improving health literacy in play and development, delivered in the form of an interactive mobile app. Future research will develop and test the efficacy of this intervention in a low resource setting in South Africa.